Нарушение нормы Леонида Андреева в драматургическом произведении – „новая драма” - Panaotović, Melina (Studia Rossica Posnaniensia, 2024)
In this article, considering the specifics of the genre, the author focuses on the new observance of the norm in the text of drama. The concept of “norm” in drama has always been interpreted in different ways, i.e. in accordance with the demands of the era, different definitions of “norm” arose. For example, at the beginning of the 20th century in Russia, a peculiar “crisis of the theater” turned out to be especially fruitful in the search for new norms (in search of a new theater). The debate about the new theater lasted, relatively speaking, for ten years: modernists, symbolists, literary groups and individual writers argued about it. Using the example of Leonid Andreyev’s “new drama”, the author discusses such deviations from the norm (previous views) as symbolism and generalization of the characters (in The life of man and Tsar Hunger), the conventionality of the place and time of action (Black masks), and the narrative of the dramatic text (The ocean). Also, the author pays attention to the specific role of the musical background and the chromatics of Andreyev’s works of the “new theater”. Listed as “new plays” during the discussions on the future path of Russian dramatic literature and Russian theater in general, these plays represent the writer’s search for a new dramatic expression, which would later become known in literature as Leonid Andreyev’s “substantial theater”.